2014
DOI: 10.1016/j.ism.2014.09.001
|View full text |Cite
|
Sign up to set email alerts
|

Audit Committee and Financial Distress in the Middle East Context: Evidence of the Lebanese Financial Institutions

Abstract: International audienceThe purpose of this paper is to detect the impact of audit committee characteristics on Lebanese financially distressed and non-distressed banks. Four characteristics of the audit committee are being examined; size, composition, frequency of meeting and financial expertise. The sample includes 54 ebanese banks with fiscal years-end between 2009 and 2011. The financially distressed and non-distressed banks have been identified from bank profitability. Our Results show that the financial di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
40
0
18

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(61 citation statements)
references
References 34 publications
3
40
0
18
Order By: Relevance
“…AUDIT has a positive influence on ROA in line with research by and Salloum et al (2014). Audit Committee is a supervisory mechanism that can improve the financial performance of banking companies.…”
Section: Resultssupporting
confidence: 59%
See 1 more Smart Citation
“…AUDIT has a positive influence on ROA in line with research by and Salloum et al (2014). Audit Committee is a supervisory mechanism that can improve the financial performance of banking companies.…”
Section: Resultssupporting
confidence: 59%
“…Audit Committee is a supervisory mechanism that can improve the financial performance of banking companies . Results from paper by Salloum et al (2014) is an added value to corporate governance in banking companies and demonstrates the importance of the audit committee's impact on financial performance. Audit committee size found Al-Matari et al (2012) to have a significant relationship with the performance of the company, but it went against what expected.…”
Section: Introductionmentioning
confidence: 89%
“…Audit committee, which includes the size and the number of frequency meeting, can have either a significant and positive impact on firm value (Kyereboah-Coleman, 2008;Siallagan & Machfoedz, 2006;Yasser, 2011) or have a significant inverse relationship with financial reporting and firm value (Abbott & Parker, 2000;Carcello & Neal, 2003;Klein, 2002;Salloum, Azzi, & Gebrayel, 2014;Wright, 1996). Further, it can also have no impact on firm value (Susanti, Rahmawati & Aryani, 2010).…”
Section: Literature Reviewmentioning
confidence: 99%
“…This result shows that although there is a relationship between the two variables, the predictive power of corporate governance on companies' performance is too low to be meaningful. Salloum, et al(2014) aimed to highlight the impact of audit committee characteristics on Lebanese financially distressed and non-distressed banks. They examined four characteristics of the ISSN 1946-052X 2015 ajfa.macrothink.org 218 audit committee (i.e.…”
Section: Literature Reviewmentioning
confidence: 99%
“…For example, Salloum, Azzi, Gebrayel (2014)found that the financial distress of banks has a significant negative relation with the meeting frequency of the audit committee. Geiger and Rama (2006) asserted that the big audit firms provide a high quality report in terms of producing lower errors compared with the non-big audit firms.…”
Section: Introductionmentioning
confidence: 99%